2005
DOI: 10.1021/jp0580524
|View full text |Cite
|
Sign up to set email alerts
|

Dual Control Mechanism in a Belousov−Zhabotinskii (B−Z) Oscillator with Glucose and Oxalic Acid as a Double Substrate

Abstract: Oscillations in a Belousov-Zhabotinskii (B-Z) system having oxalic acid (OA) and glucose (G) as a mixed organic substrate, neither of which acts as a bromine scavenger, have been investigated. Studies have been performed for (i) varying the concentration of G while keeping the OA concentration fixed and (ii) varying OA but keeping G fixed in a batch reactor. In both cases upper and lower critical limits occur, between which oscillations are observed. Both single and double frequency oscillations have been obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Moreover, the reaction mechanism and description of pattern formations can be explained by fundamental BZ chemistry. [22][23][24][25][26][27][28][29] This suggests that, with trace amounts of Ce 4+ (or Fe 2+ ), acting as catalyst and in acidic BrO 3 À , the AA (or SA) is oxidized. Some intermediates are also formed whose concentration is found to vary periodically as a function of time.…”
Section: Development Of Concentric Ringsmentioning
confidence: 99%
“…Moreover, the reaction mechanism and description of pattern formations can be explained by fundamental BZ chemistry. [22][23][24][25][26][27][28][29] This suggests that, with trace amounts of Ce 4+ (or Fe 2+ ), acting as catalyst and in acidic BrO 3 À , the AA (or SA) is oxidized. Some intermediates are also formed whose concentration is found to vary periodically as a function of time.…”
Section: Development Of Concentric Ringsmentioning
confidence: 99%
“…The first report about oscillating CL reaction catalyzed by Ru(bpy) 3 2+ was proposed in 1982 by Bolletta et al, [24] which was also the first example of oscillating CL reaction in the liquid phase. However, further studies about this oscillating CL reaction have seldom been reported.…”
Section: +mentioning
confidence: 97%
“…Since there are some obvious similarities between chemical oscillating systems and life processes that generally exhibit oscillatory behaviors, the investigation of the oscillating systems is of considerable interest. While a substantial number of chemical oscillators are known and have been widely used in analytical detection, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] relatively few oscillating chemiluminescence (CL) reactions in the liquid phase have been described. [15][16][17][18][19][20] Recently, owing to the particular photochemical and photophysical properties of the tris(2,2′-bipyridine)ruthenium(II) [Ru(bpy) 3 2+ ] CL reagent, [21][22][23] the Ru(bpy) 3…”
Section: Introductionmentioning
confidence: 99%
“…The Marburg-Budapest-Missoula (MBM) [22] model includes both negative feedback loops (bromous acid-bromide ion Oregonator type and bromine dioxide-organic free radicals type feedback) deals only with cerium catalyzed system. A detailed study of the BZ reaction with aliphatic compounds like oxalic acid [23], malonic acid [24][25][26], citric acid [4], glucose [27], pyrocatechol [28] and ketones viz. cyclohexanone [29] and acetone [30] in wide range of concentrations of the substrates have been reported.…”
Section: Effect Of Manganese Salts On An Oscillatory Chemical Reactiomentioning
confidence: 99%